2009
DOI: 10.1111/j.1530-0277.2008.00847.x
|View full text |Cite
|
Sign up to set email alerts
|

Low Bone Mineral Density and Impaired Bone Metabolism in Young Alcoholic Patients Without Liver Cirrhosis: A Cross‐Sectional Study

Abstract: Our study indicates that younger alcoholic patients without other diseases may suffer from an increased risk to develop low BMD and a disturbance of vitamin D metabolism. Nutritional factors or less exposure to sunlight may play an important role in bone loss in young alcoholic patients. BMD measurement and assessment of bone metabolism should be considered in all patients with chronic alcoholism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
48
3
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(57 citation statements)
references
References 30 publications
(36 reference statements)
4
48
3
1
Order By: Relevance
“…Researches from Austria and Europe showed that chronic heavy alcohol use, especially during adolescence and young adult years by interfering calcium absorption, can dramatically affect bone health and increase the risk of osteoporosis later in life (Malik et al, 2009;De Vernejoul et al, 1983). However, this study observed alcohol intake had no significant association with the development of osteoporosis; this may be attributed to the fact that many people hesitate to tell the truth about the frequency and amount of alcohol intake due to high religiosity in the study area.…”
Section: Discussioncontrasting
confidence: 73%
“…Researches from Austria and Europe showed that chronic heavy alcohol use, especially during adolescence and young adult years by interfering calcium absorption, can dramatically affect bone health and increase the risk of osteoporosis later in life (Malik et al, 2009;De Vernejoul et al, 1983). However, this study observed alcohol intake had no significant association with the development of osteoporosis; this may be attributed to the fact that many people hesitate to tell the truth about the frequency and amount of alcohol intake due to high religiosity in the study area.…”
Section: Discussioncontrasting
confidence: 73%
“…Epidemiological studies in alcoholics of both genders report significant decreases in bone mineral density (BMD) and increased bone fractures and osteoporosis risk compared with nondrinkers (Clark et al, 2003;Malik et al, 2009;Pasoto et al, 2011;Wuermser et al, 2011), which is related to changes in bone turnover, particularly decreased bone formation and increased bone resorption (Dai et al, 2000;Alvisa-Negrín et al, 2009;Callaci et al, 2010;Díez-Ruiz et al, 2010). Previously, we have reported significant decreases in tibial and femoral BMD after chronic ethanol (EtOH) consumption in cycling female rats receiving isocaloric diets via intragastric infusion [total enteral nutrition (TEN)] Chen et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Insufficiency of vitamin D and decrease of sexual steroids like magnesium and phosphate, are also related. These hormones are commonly known to have positive effects on osteoblasts [17,18].…”
Section: Discussionmentioning
confidence: 99%